A Critical Review On Fiber Reinforced Polymer Composites In Strengthening Reinforced Concrete Structure (International Journal of Innovative Research in Engineering & Management, 2022)
Fibre reinforced polymer (FRP)  composites still give designers the ability to deliver  innovativeand intelligent solutions to beat the ever growing aging problems in the infrastructure. Since it's  been over50 years since the introduction of FRP materials  to the development business, this paper presents a  progressivereview of historic and up-to-datedevelopments  of FRP in strengthening and rehabilitation  engineeringapplications. This review highlights a fewof  the classic and modern experimental, numerical, and  analyticalstudies related to the mixing of FRPs into  buildings, among different structures. The discussion  representedherein aims at covering the application of FRP  systems in concrete structural members and conjointly  highlightsthe performance of FRPs (including bonding  agents) beneath extreme conditions like elevated  temperature,saline atmosphere, and cycles of physical  change and thawing. This paper conjointly presents a  collective perspective onseveral limitations, challenges, and analysis desires related to flourishing, property, and  sturdy implementation of FRPs in civil infrastructure.
Keywords: Concrete; fiber; polymer; reinforced; strengthening